The unbearable ambiguity of the Border - Ortíz, Victor M. (Social justice, 2001)
Part of a special issue on immigration and boundary policing in an era of globalization. The writer discusses the abuses carried out by the Immigration and Naturalization Service along the U.S.-Mexican border. He examines the contextual dimension that fosters and sustains these abuses in order to understand the pervasive incongruent practices and representations connected to the border region. He offers various ethnographic reflections to demonstrate that the abuses do not happen only in regard to INS practices. He argues that economic and geopolitical developments such as xenophobia, the demographic growth of the Latino population, the maquiladora industry, and the North American Free Trade Agreement all influence the abuses.